Improved Supply Chain Management in E-Pharmacy Supply Chain Using Machine Learning Intelligence - Gobinath, T.; X., Anitha Mary; Maheshwari, Shikha; Madhavi, N. Bindu; Rafeeq, Md.; Kannan, G. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The applications of artificial intelligence and machine learning will eventually be useful in every industry. By putting any of these strategies into practice at work, you can make your work more productive in any area. Both of these can be utilized in the context of the retail pharmaceutical industry. However, their uses are very different from one another in a number of important respects. Not only is it feasible to anticipate the health of the patient with the assistance of the machine learning prediction model, but it is also possible to forecast the therapy that will be delivered to them. When AI technologies are used for automation, the amount of work that has to be done with the same number of resources can be accomplished with fewer persons working and with fewer resources. In this paper, we develop an improved supply chain management in e-pharmacy supply chain using the assistance of the machine learning intelligence. The machine learning intelligence using supervised learning offers an improved support on the supply chain for the drugs to be transported, tracked and delivery to the customers. The simulation in conducted to test the efficacy of the supply chain management of e-pharmacy drugs using machine learning algorithm. The simulation is conducted to test the efficacy of the model against various other models. The results of simulation shows that the proposed method achieves higher rate of accuracy than the other methods.